Cultural adaptation of the Pieper-Zulkowski Pressure Ulcer Knowledge Test for use in Brazil - Soraia Assad Nasbine Rabeh; Simon Palfreyman; Camilla Borges Lopes Souza; Rodrigo Magri Bernardes; Maria Helena Larcher Caliri
ABSTRACT Objective: To carry out the cultural adaptation of the Pieper-Zulkowski Pressure Ulcer Knowledge Test (PZ-PUKT) for use in Brazil and analyze the internal consistency of the adapted version. Method: This was a methodological study. The PZ-PUKT is a knowledge test consisting of 72 items, divided into: prevention, staging, and wound description. The present study was developed in two phases: (1) translation of the questionnaire from English to Brazilian Portuguese, back-translation, and assessment of equivalence between the original and back-translated version by an expert panel; (2) pre-testing with nurses. Results: The questionnaire showed face and content validity according to the opinions of the experts. Cronbach's alpha for the total test score was higher than 0.70. The adapted version presented satisfactory internal consistency for the studied sample. Conclusion: The adapted version of the instrument for Portuguese can be used in intervention studies as a tool to measure "nursing knowledge about pressure injury/ulcers" as a dependent variable.